Clinical relevance of the study of hepatitis B virus covalently closed circular DNA. (January 2016) - Kumar, Rajneesh; Pérez‐del‐Pulgar, Sofía; Testoni, Barbara; Lebossé, Fanny; Zoulim, Fabien
Abstract: Hepatitis B virus (HBV) remains a public health concern with 240 million people affected worldwide. HBV is an hepadnavirus that replicates its genome in hepatocytes. One of the key steps of the viral life cycle is the formation of cccDNA – covalently closed circular DNA – in the nucleus, the equivalent of a viral mini‐chromosome that acts as a template for subsequent virus replication. Current antiviral medications are not effective in eradicating cccDNA, which can persist in the infected liver even in the absence of detectable HBV DNA or HBsAg in the blood. cccDNA cannot be measured in serum, and few surrogate markers have been proposed. Persistent cccDNA has been associated with various clinical events, including viral reactivation induced by immunosuppressive therapies, HBV recurrence after liver transplantation and hepatocellular carcinoma (HCC). cccDNA remains the main target to achieve a cure of HBV infection, thus extensive efforts are being made to develop new antiviral concepts to degrade or silence cccDNA.